Between Central Europe and Europe (Slovenians and European concepts) - Lazarević, Žarko (Great Theorists of Central European Integration, 2023)
In the case of the Slovenians, it is difficult to discuss elaborate European concept at various levels before the last quarter of the 20th century. As a rule, these concepts represented a summary or imitation of others that circulated in the European territory. Even if the Slovenians did not actively contribute to the development of European political concepts, they nevertheless learned about them and recognised themselves in them (or not). Perhaps they did not conceive Europe as an idea, but they certainly lived it. They reflected upon Europe during a period of profound turning points and a geostrategic vacuum. The idea that integration into a supranational community was necessary to ensure smooth national development, while maintaining an open economy would enable the internationalisation of the economy to achieve greater scale, was a historical constant. KEYWORDS: Slovenia, Europe, Central Europe, European concepts, European integration, national ideology